RHCE*cE734C allele encodes an altered c antigen and a suppressed E antigen not detected with standard reagents. Issue 5 (7th September 2012) - Silvy, Monique; Barrault, Aurélie; Velliquette, Randall W.; Lomas‐Francis, Christine; Simon, Sophie; Mortelecque, Rosanna; Chiaroni, Jacques; Bierling, Philippe; Noizat‐Pirenne, France; Bailly, Pascal; Tournamille, Christophe
<x xml:space="preserve">Abstract</x> BACKGROUND: The RH blood group system has many RHCE variant alleles that have arisen through gene conversion or nucleotide changes. Two probands, with red blood cells (RBCs) that were D+C+E−c+we+ were sent to our laboratories to resolve the weak c expression. STUDY DESIGN AND METHODS: Hemagglutination tests were performed by automated and manual procedures. Genomic DNA analysis was performed by sequencing of Exons 1 to 10 of RHCE and RHD. RESULTS: The probands' RBCs did not react with standard monoclonal anti‐E reagents from Bio‐Rad, Diagast, DiaMed, Immucor, Ortho, and Quotient. The RBCs reacted variably with anti‐c reagents from Diagast, DiaMed, Immucor, or Ortho and did not react with the Quotient anti‐c reagent. Surprisingly, sequencing results of RHCE showed the presence of C/G at Position 676 (E/e polymorphism) and the association of the E polymorphism with a 734T>C transition in Exon 5 of the RHCE, encoding a Leu245Pro amino acid substitution in the mature RhcE polypeptide. Replacement of leucine 245 by proline in the eighth transmembrane domain of the RhcE protein may have a steric effect on the protein such that most anti‐E reagents do not bind and the interaction between anti‐c and c antigen is also affected. CONCLUSION: We report a novel RHCE*cE allele, RHCE*cE734C, which was assigned the provisional ISBT allele name RHCE*cE.14 or RHCE*03.14. It was found in two probands whose RBCs had weakened c expression and typed E− with conventional anti‐E reagents. These data, once again, highlight the fact that the genotype does not always reflect the phenotype.